Narrative, Digitality, Well-Being - O’Sullivan, Michael. author. (orcid)0000-0002-3621-9333 Link aut Link
XIII, 188 p. 3 illus., 2 illus. in color.
Keywords: Narrative, Digitality, Well-Being Narrative, Digitality, Wellbeing adopts a transdisciplinary approach in exploring new forms of narrative that have emerged in a digital age, an age of new online practices that are both associated with increased risk and enhanced sense of identity. The book examines new literary narratives, new philosophies of digitality, and new approaches to cross-disciplinary work between narrative theory and psychology in the context of digital environments, interactions, and practices. It also explores through textual analysis and quantitative and qualitative analysis how users shape and understand these new narrative interactions for their own wellbeing and how educators assess the relationships between narratives and wellbeing in the classroom and lecture theatre. The book argues that theories of narrative need to be updated to account for these new forms of narrative and to account for the new ways narrative is employed by users to enhance wellbeing. Michael O’Sullivan is an Associate Professor in the Department of Languages and Literature at United Arab Emirates University and Research Associate at the Department of English of the Chinese University of Hong Kong. He is a member of the British Psychological Society and the Irish Society of Guidance Counsellors and has many years experience counselling and advising students in colleges, schools and universities in Ireland, the UK, Japan, Hong Kong and the UAE. Michael has published 15 books in the fields of literature, education studies and philosophy. Recent books include Cloneliness: on the reproduction of loneliness (2019/2021); Weakness: a literary and philosophical history <(2012/2014); and Academic barbarism, universities and inequality (2016/2018). His first novel Lockdown Lovers was published with Penguin in 2021.